Some Peculiarities of Classification of Pun and Translation (In Examples of Shakespeare's Poetic Texts) - Mizrabova Jeren (Peerian Journals Publishing, 2022)
Many problems and tasks in the science of translation are still waiting to be solved. The issue of translation of the pun (word play) is also one of them. Although much research has been done in this field in foreign science to date, it has not yet been decided on the properties of a device like pun and it is acknowledged that there are different opinions about its etymology. Wordplay is a multifaceted phenomenon that, performing a number of functions, occupies a special place in the works of W. Shakespeare. Wordplay is closely related to the content of the plays and is used to express dramatic conflicts. With the above mentioned device’s help, both serious and comic dialogues are conducted, to which she gives sharpness and wit, helps to express irony and humor, and also serves as a means of portraying characters. The important dramatic role of William Shakespeare's play on words requires special attention from researchers and adequate reproduction in translation
Keywords: wordplay; translation; classification; irony